Strategies for Increasing Teacher Competence and the Quality of Islamic Education Learning at State Middle School 8 Medan - Sutarman, Sutarman; Binti Salleh, Rosmalily (PDPI (Perkumpulan Dosen Peneliti Indonesia), 2023)
This study aims to determine: Strategies for increasing teacher pedagogical competence. Learning quality improvement strategy. Obstacles that arise are faced by school principals in improving teacher performance in the learning process and Islamic Religious Education at State Middle School 8 Medan. The research method uses a qualitative approach. Data collection techniques through interviews, observation, and documentation studies. The results of the strategy as a school principal's program in improving the learning process and quality of education are: (1). Improving teacher expertise in carrying out the learning process (2). Optimizing the use of learning media in the learning process and the quality of education. (3). Supervise in overcoming problems related to unprofessionalism by teachers in carrying out assignments (4). Collaborating with stakeholders and the community Implementing strict discipline for all components of the school. Obstacles that often arise and are faced by school principals in improving teacher performance in the learning process and quality of education are: There are PAI teachers who are not creative in carrying out the learning process to improve the quality of education with religious programs. Students have not been consistent in carrying out religious learning. Differences in students become obstacles to the development of learning aspects. Lack of awareness on the part of parents in determining students in the learning process.